The Role of the Internet in Promoting Mental Health: Evaluating the Internet's Role in Providing Psychological Treatment and Support Services During Crises and Wars in Lebanon - fadlalah, Mohamad Ibrahim; jaber, Professor Dr. Mohamad (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2025)
This study delves into the role of internet-based platforms in providing mental health support during crises and wartime situations in Lebanon. As our dependence on digital technologies grows, the internet has emerged as a vital resource for therapy, psychoeducation, and peer support. The research employs a mixed-methods quasi-experimental pretest-posttest design to assess psychological outcomes among 90 Lebanese adults utilizing online mental health services. Three key hypotheses were examined: that the internet enhances access to mental health support, alleviates psychological distress, and boosts perceived emotional support. The quantitative data were analyzed using SPSS v21. The findings reveal significant improvements in mental well-being and a decrease in distress levels, indicating that internet-based services can be a powerful tool in trauma-informed mental health care.